2020
DOI: 10.1042/bst20190338
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule ERK5 kinase inhibitors paradoxically activate ERK5 signalling: be careful what you wish for…

Abstract: ERK5 is a protein kinase that also contains a nuclear localisation signal and a transcriptional transactivation domain. Inhibition of ERK5 has therapeutic potential in cancer and inflammation and this has prompted the development of ERK5 kinase inhibitors (ERK5i). However, few ERK5i programmes have taken account of the ERK5 transactivation domain. We have recently shown that the binding of small molecule ERK5i to the ERK5 kinase domain stimulates nuclear localisation and paradoxical activation of its transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…One issue emerging from those data, as well as from the discovery of a potentially kinase-independent transcriptional function of ERK5, is whether tumor-suppressive strategies should merely target the kinase activity or additionally aim to suppress the ERK5 transcriptional capacity. Besides XMD8-92, several other small molecule inhibitors for ERK5 have been developed (reviewed in [ 128 ]). Surprisingly, recent data with novel highly specific ERK5 kinase inhibitors suggest that efficient ERK5 kinase inhibition may induce paradoxical transcriptional activation of ERK5 [ 129 ].…”
Section: Erk5 In Mechanical Stress-exposed Tissues and Mapk Inhibitor-resistant Cancersmentioning
confidence: 99%
“…One issue emerging from those data, as well as from the discovery of a potentially kinase-independent transcriptional function of ERK5, is whether tumor-suppressive strategies should merely target the kinase activity or additionally aim to suppress the ERK5 transcriptional capacity. Besides XMD8-92, several other small molecule inhibitors for ERK5 have been developed (reviewed in [ 128 ]). Surprisingly, recent data with novel highly specific ERK5 kinase inhibitors suggest that efficient ERK5 kinase inhibition may induce paradoxical transcriptional activation of ERK5 [ 129 ].…”
Section: Erk5 In Mechanical Stress-exposed Tissues and Mapk Inhibitor-resistant Cancersmentioning
confidence: 99%
“…Of particular interest amongst the putative hits identified within this screen was ERK5 (also known as MAPK7 and MEK5), as it has recently been identified as a potential oncogenic factor in several other cancers [ 6 , 7 , 8 , 9 , 10 , 11 , 18 , 19 , 20 ], and several potential therapeutic small molecule inhibitors have recently been developed [ 12 , 13 , 14 , 15 , 21 ]. To further validate ERK5 as promoting TMZ resistance in glioma cells and to discount potential off-target RNAi effects, we used siPOOLs consisting of 30 individual low nM siRNA that have been shown to give effective knockdown at low total nM concentrations ( Figure S1B ) with reduced off-target effects [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, in most of these cases, ATP-competitive binding of the inhibitors induce conformational changes, which activate noncatalytic functions of these kinases. 37 , 68 …”
Section: Discussionmentioning
confidence: 99%
“… 29 Studies on inhibitors of other protein kinases have however revealed that some Type I kinase inhibitors are prone to activate noncatalytic functions of the target protein. 35 37 For the clinical translation of the mainly genetic-based proposal of targeting MNKs as a promising new strategy in oncology, it is therefore desirable to identify non-ATP-competitive inhibitors to evaluate different modes of kinase inhibition in preclinical and clinical settings.…”
Section: Introductionmentioning
confidence: 99%